Development of a Pre-Marital Integrative Training Package Based on Bowen and Savickas Models and Comparison of Its Effectiveness with the SYMBIS Approach on Self-Awareness and Marital Choice Orientation - Raki, Ali; Atashpour, Seyed Hamid; Golparvar, Mohsen (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The study aimed to compare the effectiveness of an integrative pre-marital training package based on Bowen's intergenerational theory and life design model with the SYMBIS approach on marital choice orientation.Methods: A quasi-experimental research design with a pretest-posttest-follow-up model and two experimental groups and one control group was utilized. The statistical population consisted of university students in Isfahan. The sample included 45 female students selected through convenience sampling based on inclusion and exclusion criteria and randomly assigned to three groups (integrative training group, SYMBIS group, and control group), each containing 20 participants. The experimental groups received eight 90-minute training sessions, while the control group was placed on a waiting list. All three groups completed research instruments at the pretest, posttest, and follow-up stages. The research instrument was the Marital Choice Orientation Questionnaire (Yousefi, 2023). Data were analyzed using repeated measures ANOVA.Findings: Results indicated that both the integrative training group and the SYMBIS group significantly influenced marital choice orientation (F = 15.5, P = 0.001), and this effect remained stable during the follow-up phase (P < 0.05).Conclusion: The findings revealed that both methods had a significant and comparable impact on improving the dependent variable, suggesting their utility in enhancing marital choice orientation.